A Role for Nociceptive, Myelinated Nerve Fibers in Itch Sensation - Ringkamp, Matthias; Schepers, Raf J.; Shimada, Steven G.; Johanek, Lisa M.; Hartke, Timothy V.; Borzan, Jasenka; Shim, Beom; LaMotte, Robert H.; Meyer, Richard A. (The Journal of neuroscience, 2011)
Despite its clinical importance, the underlying neural mechanisms of itch sensation are poorly understood. In many diseases, pruritus is not effectively treated with antihistamines, indicating the involvement of nonhistaminergic mechanisms. To investigate the role of small myelinated afferents in nonhistaminergic itch, we tested, in psychophysical studies in humans, the effect of a differential nerve block on itch produced by intradermal insertion of spicules from the pods of a cowhage plant ( Mucuna pruriens ). Electrophysiological experiments in anesthetized monkey were used to investigate the responsiveness of cutaneous, nociceptive, myelinated afferents to different chemical stimuli (cowhage spicules, histamine, capsaicin). Our results provide several lines of evidence for an important role of myelinated fibers in cowhage-induced itch: (1) a selective conduction block in myelinated fibers substantially reduces itch in a subgroup of subjects with A-fiber-dominated itch, (2) the time course of itch sensation differs between subjects with A-fiber- versus C-fiber-dominated itch, (3) cowhage activates a subpopulation of myelinated and unmyelinated afferents in monkey, (4) the time course of the response to cowhage is different in myelinated and unmyelinated fibers, (5) the time of peak itch sensation for subjects with A-fiber-dominated itch matches the time for peak response in myelinated fibers, and (6) the time for peak itch sensation for subjects with C-fiber-dominated itch matches the time for the peak response in unmyelinated fibers. These findings demonstrate that activity in nociceptive, myelinated afferents contributes to cowhage-induced sensations, and that nonhistaminergic itch is mediated through activity in both unmyelinated and myelinated afferents.